The Brief Text in Modern Arabic Literature: From Article to Signature (An Analytical Study of Genre) - Talib Al-Asadi, Prof. Dr. Muhammad (Basra studies journal, 2024)
This study seeks to explore the characteristics of the brief text in our modern Arabic literature, with its various patterns, culminating in its terminological transformations and representations. The brief text has established a foothold for its discourse that competes with expressive forms that extend in the print space, forming a pattern characterized by conciseness and economy in the number of text words, a remarkable literary phenomenon that cannot be denied or overlooked. It strives to possess its own uniqueness and features. The brief text can be a poetic or narrative structure, similar to long texts if provided with a skilled creator of literary craft capable of conveying its connotations to the recipient and attracting them to the text area to explore the layers of discourse. The study follows the threads of this study to its conclusions, demonstrating to the recipient how the brief text has been dealt with – in many instances – as an emerging discourse, rather than as a product of successive textual transformations, to the extent that some of its proponents and recipients of its aesthetic charm claim leadership in its production, without relying on historical awareness of the experience or critical awareness of discourse. This has been coupled with confusion in terminology. The study seeks to clarify and direct it within the limits of what the contemporary poetic and critical scene has provided in terms of components and evidence. The discourse of the brief did not emerge in our modern Arabic literature from nothingness, but rather was preceded by concise formations that must be taken into consideration when reaching the qualitative terminations of discourse in its temporal presence, as they are paths whose arrows each contribute to the integration of the cognitive essence of concise discourse in the scene of modernity, leading to literary dualism, as the equivalent counterpart of critical dualism. The brief text we know today in our Arabic literature is the product of interaction and interconnection of distant textual origins, and others close, as both narrative and poetry have influenced each other and borrowed from each other, intertwining in their production of their genre of brevity. Therefore, we will shed light on both narrative and poetic brevities through archeological survey. It is necessary to resort to archaeology when approaching the problematics of the brief text, with its historical and qualitative connotations.